AFRICAN MUSIC BOWS IN SOME EUROPEAN MUSEUMS - (:unkn) unknown (My University, 2014)
AFRICAN MOUTHBOWS IN EUROPEAN MUSEUMS : A STUDY IN ORGANOLOGY, ACOUSTICS, MUSICOLOGY, AND ETHNOLOGY.M. François PICARD Professeur d'ethnomusicologie, université Paris-Sorbonne JURY: M. Apollinaire ANAKESA professeur d'ethnomusicologie, Université de la Guyane M. François BOREL ancien conservateur adjoint, Musée d'ethnographie de Neuchâtel M. Yves DEFRANCE HDR, directeur adjoint CFMI, Université de Rennes II M. Nicolas MEEÙS Professeur de musicologie, Université Paris-Sorbonne M. TRAN Quang-Hai ingénieur CNRS, retraité
Keywords: African Research